Heterodox modeling: practicing well-tuned provisioning or commoning with networked multi-agent environments - Shintaro Miyazaki (Review of Evolutionary Political Economy, 2023)
Market-driven, profit-oriented, mainstream neoclassical economics is increasingly being challenged by alternative approaches such as heterodox economics. This article contributes to broader discussions in this field, especially of social provisioning, and suggests that integrating perspectives from the overlapping fields of media history and history of economy could not only provide valuable insights and attract more supporters, but even initiate a bottom-up transformation process. Historical knowledge regarding how neoclassical economics gained mainstream status in the early postwar decades provides hints on how to popularize non-profit-driven, well-designed approaches to social provisioning, often referred to as commoning. More specifically, the article firstly addresses the necessity of a large-scale appropriation of computational methods, procedures, tools, media, and models to experiment with economic issues, which are usually applied mostly by mainstream profit-driven approaches. Secondly, it presents the implications of such a practice, which I tentatively refer to as heterodox modeling, while remembering the 1960s North American context of business simulation games and their role within the large-scale effort to educate and train the newly-defined class of “business managers.” The article, thirdly, theorizes heterodox modeling as being based on a still imaginary, not-yet implemented, networked multi-agent online environment, which would integrate the modular programming of agent-based models, group exercises, role-playing, gaming, and testing of operations and processes within large-scale socio-ecological networks of commoning. Finally, the article argues not only to model heterodox economic theories, but at the same time to model in heterodox ways and highlight associated implications.
Keywords: B15; B25; B51; C63; P41; Z13; 320; Commoning; Heterodox Modeling; Gaming; Provisioning; Lifenet